Pelatihan Pembuatan Lotion Anti Nyamuk Herbal Kombinasi Daun Sereh dan Daun Pandan sebagai Upaya Perlindungan terhadap Gigitan Nyamuk pada PKK di Kelurahan Sukorejo, Kota Semarang - Anggita Dipika Wulandari; Rifda Naufa Lina; Rahmawati Salsa Dinurrosifa (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
The rainy season in Sukorejo Village, Semarang City, increases mosquito populations due to stagnant water, potentially transmitting diseases such as dengue fever, malaria, and chikungunya. The community still relies on chemical-based mosquito repellent lotions containing DEET, which carry risks of skin irritation, allergies, and potential toxicity. Natural ingredients such as lemongrass (Cymbopogon nardus) and pandan leaves (Pandanus amaryllifolius) contain active compounds—citronellal, geraniol, alkaloids, flavonoids, and polyphenols—that are effective as natural repellents. The purpose of this activity is to enhance the knowledge and skills of PKK women in utilizing lemongrass and pandan leaves for the production of safe, effective, and environmentally friendly herbal mosquito repellent lotion. The program was implemented in four stages: (1) health education on mosquito-borne diseases and active plant compounds, (2) training on herbal lotion production covering raw material selection, hygienic processing, formulation, and packaging, and (3) production assistance by the community service team. Methods included lectures, discussions, demonstrations, and hands-on practice. The program improved participants’ understanding of natural repellents and their ability to independently produce herbal lotion. The lemongrass–pandan lotion produced met safety standards, had a pleasant aroma, and was effective in protecting against mosquito bites. This training effectively increased the capacity of PKK members, reduced dependency on commercial chemical-based products, and opened opportunities for local, small-scale businesses.